Isolation, characterization, and receptor-binding protein specificity of phages PAS7, PAS59 and PAS61 infecting Shiga toxin-producing Escherichia coli O103 and O146 - Célia Pas; Lars Fieseler; Joël F. Pothier; Yves Briers (Scientific Reports, 2024)
Abstract Shiga toxin-producing Escherichia coli (STEC) is a foodborne pathogen with 6,534 annual reported cases in the EU in 2021. This pathotype generally contains strains with smooth LPS with O-antigen serogroup O157 being the predominant serogroup in the US. However, non-O157 STEC serogroups are becoming increasingly prevalent. Here we announce the complete genomes of three newly isolated phages that infect STEC serogroups O103 and O146, namely Escherichia phages vB_EcoP_PAS7, vB_EcoP_PAS59 and vB_EcoP_PAS61. The genome sequences revealed that they belong to three distinct genera, namely the newly proposed genus Cepavirus within the Slopekvirinae subfamily, the genus Suseptimavirus and the genus Uetakevirus, respectively. We identified the tailspikes of phages PAS7 and PAS61 as a primary specificity determinant for the O-antigens O103 and O146, respectively, and predicted their active site in silico.